Numerical Analysis of Threats to Rice Production Due to Excess Use of Chemical Fertilizers - Uzzwal Mallick; Pulak Kundu (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
Rice production, an essential source of nutrition, is vital for food security and rural livelihoods. With a rapidly growing population and limited arable land, it increasingly depends on chemical fertilizers. Overuse of these fertilizers can threaten long-term sustainability. To address this issue, a field experiment was conducted using four distinct fertilizer management strategies. By fitting parameter values to the experimental data, a new nonlinear model has been proposed to analytically and numerically investigate the effects of chemical fertilizer use in rice cultivation. The analytical framework includes the examination of the existence, uniqueness, and stability of equilibrium points using the Jacobian matrix, along with sensitivity analysis to identify the parameters that most significantly influence system behavior. Results from both field experiments and simulations showed that a 40% chemical fertilizer combined with 60% organic fertilizer resulted in the highest soil nutrient content and rice yield. Organic inputs improve soil fertility through decomposition of plant residues, but excessive use can increase soil salinity, harming rice growth. Therefore, this study recommends that fertilizers should be applied in an efficient and balanced manner to maximize crop production while maintaining long-term soil fertility, and the developed model can serve as a practical and cost-effective tool for predicting field fertility, thereby reducing the need for conducting new field experiments.